2013
DOI: 10.1139/cjb-2012-0131
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical leaf damage causes localized, but not systemic, changes in leaf movement behavior of the Sensitive Plant, Mimosa pudica (Fabaceae) L.

Abstract: A small number of species, including Mimosa pudica, use rapid leaf movement as a presumptive defensive strategy. How movement-based defenses change in response to mechanical damage and whether changes are localized or systemic is unknown. This is in contrast to a substantial literature describing how mechanical leaf damage can cause morphological and chemical responses within a diversity of plant species. Depending on the species and the stimuli, these chemical and morphological responses can be localized to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…They also reported great variability in hiding time between plants. Cahill Jr et al (2012) speculated that this variability in hiding time was due to changes in environmental conditions, which is what we found ( Fig. 3 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…They also reported great variability in hiding time between plants. Cahill Jr et al (2012) speculated that this variability in hiding time was due to changes in environmental conditions, which is what we found ( Fig. 3 ).…”
Section: Discussionsupporting
confidence: 75%
“…By contrast, Cahill et al (2012) reported that sensitive plants behaved in a manner localized to each leaf and Simon, Hodson & Roitberg (2016) did not explore if decisions on whether to photosynthesize were made on a leaf or plant level. When Cahill Jr et al (2012) damaged leaflets, the hiding time of that leaf increased, but surrounding leaves remained unaffected, indicating that response to damage is highly localized. This reaction may be limited to response to damage as we were unable to repeat these results when we manipulated light.…”
Section: Discussionmentioning
confidence: 98%
“…This response is generally believed to function as a defence against herbivory, possibly by startling or physically displacing herbivores, reducing the apparency of the leaves, or enhancing the display of defensive thorns (Braam, 2005). Consistent with this hypothesis, leaf wounding has been shown to significantly prolong the time until reopening of damaged leaves (but not of leaves more distant from the site of damage) (Cahill et al, 2012). Another recent study demonstrated that closed leaves reopen sooner under low-light conditions, suggesting a trade-off between the acceptance of predation risk and the opportunity costs of reduced photosynthesis by closed leaves under conditions of energetic stress (Jensen et al, 2011).…”
Section: Detection Of Herbivoresmentioning
confidence: 89%
“…The adaptation and proliferation of this weed is due to factors such as large seed production and anti-herbivore defenses (this occurs with the leaves rapid movement and the petiole decline) [25,[32][33][34]. These leaves are also in response to stressors such as electrostimulation, wound, wind, vibration, touch, drought, change of lighting, and warm or cold stimuli, which help the plant to protect itself or adapt to a particular environment condition where the vegetable is inserted [25,27], such as at light levels [25,27,28].…”
Section: Malícia (Mimosa Pudica L)mentioning
confidence: 99%